A new birthweight reference in Guangzhou, southern China, and its comparison with the global reference. Issue 12 (24th June 2014) - He, Jian-Rong; Xia, Hui-Min; Liu, Yu; Xia, Xiao-Yan; Mo, Wei-Jian; Wang, Ping; Cheng, Kar Keung; Leung, Gabriel M; Feng, Qiong; Schooling, C Mary; Qiu, Xiu
Abstract : Objective: To formulate a new birthweight reference for different gestational ages in Guangzhou, southern China, and compare it with the currently used reference in China and the global reference. Design and setting: All singleton live births of more than 26 weeks' gestational age recorded in the Guangzhou Perinatal Health Care and Delivery Surveillance System for the years 2009, 2010 and 2011 (n=510 837) were retrospectively included in the study. In addition, the study sample was supplemented by all singleton live births (n=3538) at gestational ages 26–33 weeks from 2007 and 2008. We used Gaussian mixture models and robust regression to exclude outliers of birth weight and then applied Generalized Additive Models for Location, Scale, and Shape (GAMLSS) to generate smoothed percentile curves separately for gender and parity. Results: Of infants defined as small for gestational age (SGA) in the new reference, 15.3–47.7% (depending on gestational age) were considered appropriate for gestational age (AGA) by the currently used reference of China. Of the infants defined as SGA by the new reference, 9.2% with gestational ages 34–36 weeks and 14.3% with 37–41 weeks were considered AGA by the global reference. At the 50th centile line, the new reference curve was similar to that of the global reference for gestational ages 26–33 weeks and above the global reference for 34–40 weeks. Conclusions: The new birthweight reference based on birthweight data for neonates in Guangzhou, China, differs from the reference currently used in China and the global reference, and appears to be more relevant to the local population.